Developmental Analysis of the GATA Factor HANABA TARANU Mutants in Medicago truncatula Reveals Their Roles in Nodule Formation - Xu, Yiteng; Wang, Hongfeng; Lu, Zhichao; Wen, Lizhu; Gu, Zhiqun; Zhang, Xue; Yu, Guangle; Wang, Hailong; Zhou, Chuanen; Han, Lu (Frontiers in Plant Science, 2021)
Formation of nodules on legume roots results from symbiosis with rhizobial bacteria. Here, we identified two GATA transcription factors, MtHAN1 and MtHAN2, in Medicago truncatula, which are the homologs of HANABA TARANU (HAN) and HANL in Arabidopsis thaliana. Our analysis revealed that MtHAN1 and MtHAN2 are expressed in roots and shoots including the root tip and nodule apex. We further show that MtHAN1 and MtHAN2 localize to the nucleus where they interact and that single and double loss-of-function mutants of MtHAN1 and MtHAN2 did not show any obvious phenotype in flower development, suggesting their role is different than their closest Arabidopsis homologues. Investigation of their symbiotic phenotypes revealed that the mthan1 mthan2 double mutant develop twice as many nodules as wild type, revealing a novel biological role for GATA transcription factors. We found that HAN1/2 transcript levels respond to nitrate treatment like their Arabidopsis counterparts. Global gene transcriptional analysis by RNA sequencing revealed DEGs enriched for several pathways important for nodule development including flavonoid biosynthesis and phytohormones. In addition, further studies suggest that MtHAN1 and MtHAN2 are required for the expression of several nodule-specific cysteine-rich (NCR) genes, which they may activate directly, and many peptidase and peptidase inhibitor genes. This work expands our knowledge of the functions of MtHANs in plants by revealing an unexpected role in legume nodulation.